Chromoplast differentiation in bell pepper (Capsicum annuum) fruits. (5th January 2021) - Rödiger, Anja; Agne, Birgit; Dobritzsch, Dirk; Helm, Stefan; Müller, Fränze; Pötzsch, Nina; Baginsky, Sacha
Summary: We report here a detailed analysis of the proteome adjustments that accompany chromoplast differentiation from chloroplasts during bell pepper ( Capsicum annuum ) fruit ripening. While the two photosystems are disassembled and their constituents degraded, the cytochrome b6 f complex, the ATPase complex, and Calvin cycle enzymes are maintained at high levels up to fully mature chromoplasts. This is also true for ferredoxin (Fd) and Fd‐dependent NADP reductase, suggesting that ferredoxin retains a central role in the chromoplasts' redox metabolism. There is a significant increase in the amount of enzymes of the typical metabolism of heterotrophic plastids, such as the oxidative pentose phosphate pathway (OPPP) and amino acid and fatty acid biosynthesis. Enzymes of chlorophyll catabolism and carotenoid biosynthesis increase in abundance, supporting the pigment reorganization that goes together with chromoplast differentiation. The majority of plastid encoded proteins decline but constituents of the plastid ribosome and AccD increase in abundance. Furthermore, the amount of plastid terminal oxidase (PTOX) remains unchanged despite a significant increase in phytoene desaturase (PDS) levels, suggesting that the electrons from phytoene desaturation are consumed by another oxidase. This may be a particularity of non‐climacteric fruits such as bell pepper that lack a respiratory burst at the onset of fruit ripening. Significance Statement: Chromoplast differentiation is integral to bell pepper ( Capsicum annuum ) fruit ripening and accompanied by the reorganization of an autotrophic to a heterotrophic plastid metabolism. The large‐scale quantitative proteome analysis reported here offers detailed insights into this reorganization process in a non‐climacteric fruit and allows a comparison to chromoplast differentiation in the climacteric fruit tomato ( Solanum lycopersicum ). Although both systems progress similarly, there are subtle differences with respect to redox metabolism and the timing of electron transport realignment processes.